KWL (Know, Want To Know, Learned) Method As An Effort To Increasing The Reading Capacity Of Students With Learning Difficulties - Ratih Nindea Tiyan; Cisia Padila; Rindia Nengsih (Universitas Negeri Padang, 2023)
Children who have learning difficulties really need to be considered, so that they can realize their dreams in the future. One of the initial steps in achieving this goal is that children must be able to read, because reading is a bridge so that children can get to know what they want to know. By finding out (know) what the child likes, the teacher can re-develop how to teach the child to read. Arouse children's curiosity by telling hero characters related to the problems they are facing. This study aims to accelerate students in learning, especially for students who cannot read. Research uses a literature method with a descriptive approach to reveal something as it is. Based on research conducted by children's experts in Indonesia, the interest in reading is still far from average. So that the culture of reading is still not very applied in Indonesia. Through this study, the researcher discussed how important it is for students to use the KWL method in learning so that teachers do not have difficulty in teaching reading students, especially low-grade elementary school students. This KWL method has three stages, namely the pre-reading, reading and post-reading stages. So that students can easily understand the lessons explained by the teacher in class. In addition to being easy to understand, the KWL method also makes students remember learning easily because the reading methods used are made interesting so that students' learning motivation increases.